Porous Fluids Advances in Fluid Flow and Transport Phenomena in Porous Media - Ramachandra Prasad, Vallampati (IntechOpen, 2021)
Written by authoritative experts in the field, this book discusses fluid flow and transport phenomena in porous media. Portions of the book are devoted to interpretations of experimental results in this area and directions for future research. It is a useful reference for applied mathematicians and engineers, especially those working in the area of porous media.